Adjuvant Formulations Possess Differing Efficacy in the Potentiation of Antibody and Cell Mediated Responses to a Human Malaria Vaccine under Selective Immune Genes Knockout Environment - Hui, George S. (2008)
Infections and chronic diseases can alter the host’s immunological balance or result in immuno-deficiencies. We hypothesize that this may also affect the performance of vaccine adjuvants. Accordingly, the potency and adjuvanticity of eight adjuvant formulations based on Montanide ISA720, MF59, monophosphoryl lipid A (MPL), QS21 (saponin derivative), MPL-SE (stable emulsion of a MPL derivative), and MPL-AF (MPL in aqueous formulation) were studied in immune gene knockout mice, IFN-γ −/−, IL-4 −/−, and STAT6 −/−, using the P. falciparum MSP1 vaccine, P30P2MSP1-19 as a model immunogen. The adjuvants showed preferential requirements for the immune mediators to induce immune responses to MSP1-19, and the effects were formulation-specific. While emulsion-type adjuvants were highly effective in mice, their potency was more readily suppressed by immune knockouts; and additions of immunomodulators were required to restore efficacy. Formulated adjuvants had characteristics distinct from their individual components, and multi-components formulations were not necessarily superior. We conclude that perturbation of immune environments will have measurable impact on adjuvant’s potency. Evaluation of adjuvants in immune knockout models may be a supplementary approach to measure and compare adjuvants’ efficacy, and to further unveil their distinct biological activities.